(untitled) (Actualizaciones en Sida e Infectología, 2023)
Background: Coinfection with tuberculosis and COVID-19 has been shown to have a worse clinical course. Protective immunity is weakened in this situation, leading to failure to control both infections, reactivation of latent forms of TB and exacerbated progression of active cases. Furthermore, corticosteroid therapy used in the treatment of severe COVID-19 infections can lead to immunosuppression and precipitate TB progression. Objectives: To describe the clinical characteristics, presentation and evolution of critically ill patients with COVID-19 and tuberculosis co-infection. To evaluate the incidence and lethality of COVID-19 and tuberculosis association in intensive care. Materials and methods: A retrospective, descriptive study was conducted. Twelve medical records of patients aged 18 years or older admitted to intensive care with a diagnosis of COVID-19 during the period January 2020 to July 2022 were reviewed. Descriptive statistics were used. Results and discussion: Out of a total of 1014 medical records, 12 patients were found with co-infection (incidence 0.011). The global intensive care case fatality was 75%, at 45 days it was 83.3%. This was twice the overall case fatality of non-co-infected COVID-19 patients admitted during the same period (75% versus 37%). Patients requiring admission to mechanical ventilation had a 100% case fatality and those with acquired immunodeficiency virus infection had a 100% case fatality. It is important to describe the findings and to alert to the worse evolution of those patients presenting with this association, in order to improve management and recommend searching for co-infection when clinical criteria require it.